Analisis Potensi dan Nilai Kelayakan Daya Tarik Objek Wisata Alam Hutan Mangrove Pulau Pannikiang - Irma - sribianti (Program Studi Kehutanan Universitas Muslim Maros, 2021)
The purpose of this study was to determine the potential attraction of mangrove forest natural attractions and to determine the feasibility value of the attractiveness of mangrove forest natural attractions on Pannikiang Island, Madello Village, Balusu District, Barru Regency, South Sulawesi Province. The method of data analysis in this study is guided by the Guidelines for Analysis of Operational Areas for Objects and Natural Tourism Attractions (ADO-ODTWA) of the Directorate General of Forest Protection and Nature Conservation in 2003. Data were analyzed using scoring in accordance with the criteria contained in the Guidelines for Analysis of Object Operation Areas and Nature Tourism Attractions from the Directorate General of Forest Protection and Nature Conservation in 2003. Calculations for each of these criteria use tabulations where the numbers are obtained from the results of the assessment whose weight values ​​are guided by the Assessment of Operational Areas of Objects and Natural Tourism Attractions of the Directorate General of Forest Protection and Nature Conservation 2003. Ecotourism Feasibility Assessment Method with a predetermined value for each criterion. The results of the feasibility assessment of the natural attractions of mangrove forests on Pannikiang Island, Madello Village, Balusu District, Barru Regency deserve to be developed as a natural tourist attraction destination with a feasibility level of 72.31%